Role of drugs in determining risk behaviours and HIV status among drug users in rehabilitation centers in Malaysia - Shanmugam, Thana Sehgaran (1999)
This study assess whether the type of drug used us related to HIV infection and risk behaviours among drug users who were residents in two rehabilitation centers in Malaysia between September 1, 1997 - January 5, 1998. All study subjects were selected based on criterion that they were using heroin only or morphine only or both morphine and heroin from medical review. They were interviewed by using a standard questionnaire. Their relationship to HIV infection and risk behaviours were analyzed using two-way frequency tabulation.The type of drug used was associated with risk behaviours and HIV infection. These risk behaviours were sex activities, intravenous use, booting and sex with IDU. Heroin users were less likely to have these risk behaviours than users of both heroin and morphine.The type of drugs used also was associated with booting after controlling for sex with IDU. But, type of drug used and needle use was not associated after controlling for sex with IDU.The study found that effect of type of drug used on HIV infection was mediated by needle use and booting. Type of drug used and HIV infection was also related after controlling for sex with IDU.